Ricerche archeologiche a Sant'Andrea di Loppio (Trento, Italia) : l'area della chiesa - Maurina, Barbara, (Archaeopress Archaeology, 2020)
This is the second volume presenting results of archaeological investigations on Isola di Sant'Andrea, located in the basin of Lake Loppio (Italy), with finds ranging from prehistory to the First World War. This volume considers the results of the archaeological research in the area of the church of St. Andrew (Sectors C and C1).